Exploratory study of perceived brand-image inconsistency in traditional versus Internet-based promotions. - Neo, Yen Leng. (2008)
This paper attempts to explore whether brands (in the fastfood and handphone industries) have consistent online and offline brand images. The nature and implicationsof any inconsistencies found are reviewed.